Supervisory Behavior and Employee Engagement in The Public Sector - Gangaram Biswakarma; Anu Sedai (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This research aims to explore the extent to which supervisory behavior impacts employee engagement in Nepalese public organizations, highlighting the importance of effective supervision in ensuring a motivated and committed workforce, which is essential for successfully implementing government policies and service delivery. A purposive sampling method was used to select 200 employees from various public service organizations, with 151 valid responses collected through structured questionnaires. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4, which was chosen due to its ability to handle non-normal data. The study reveals that supervisory behavior significantly affects employee engagement in Nepal's public sector. Key factors include job management, leadership, communication, thoughtfulness, and social and emotional support. The research emphasizes the need for firms to regularly monitor and measure these actions, as they impact employee engagement, employee well-being, organizational efficiency, and performance.